Transfer of the ph1b Deletion Chromosome 5B From Chinese Spring Wheat Into a Winter Wheat Line and Induction of Chromosome Rearrangements in Wheat-Aegilops biuncialis Hybrids - Edina Türkösi; László Ivanizs; András Farkas; Eszter Gaál; Klaudia Kruppa; Péter Kovács; Péter Kovács; Éva Szakács; Kitti Szőke-Pázsi; Mahmoud Said; Mahmoud Said; Petr Cápal; et al. (Frontiers in Plant Science, 2022)
Effective utilization of genetic diversity in wild relatives to improve wheat requires recombination between wheat and alien chromosomes. However, this is suppressed by the Pairing homoeologous gene, Ph1, on the long arm of wheat chromosome 5B. A deletion mutant of the Ph1 locus (ph1b) has been used widely to induce homoeologous recombination in wheat × alien hybrids. However, the original ph1b mutation, developed in Chinese Spring (CS) background has poor agronomic performance. Hence, alien introgression lines are first backcrossed with adapted wheat genotypes and after this step, alien chromosome segments are introduced into breeding lines. In this work, the ph1b mutation was transferred from two CSph1b mutants into winter wheat line Mv9kr1. Homozygous genotypes Mv9kr1 ph1b/ph1b exhibited improved plant and spike morphology compared to Chinese Spring. Flow cytometric chromosome analysis confirmed reduced DNA content of the mutant 5B chromosome in both wheat genotype relative to the wild type chromosome. The ph1b mutation in the Mv9kr1 genotype allowed wheat-alien chromosome pairing in meiosis of Mv9kr1ph1b_K × Aegilops biuncialis F1 hybrids, predominantly with the Mb-genome chromosomes of Aegilops relative to those of the Ub genome. High frequency of wheat-Aegilops chromosome interactions resulted in rearranged chromosomes identified in the new Mv9kr1ph1b × Ae. Biuncialis amphiploids, making these lines valuable sources for alien introgressions. The new Mv9kr1ph1b mutant genotype is a unique resource to support alien introgression breeding of hexaploid wheat.